High winter survival rate of acorn ants inside artificial nest sites (Hymenoptera: Formicidae) - Mitrus, Sławomir (Fragmenta entomologica, 2022)
Although most species of ants overwinter underground to avoid low temperatures, the acorn ants of the genus Temnothorax remain in nests situated at ground level. During a field experiment, I studied the winter mortality of acorn ants in nest sites situated aboveground, as well as in sites experimentally buried in the soil. Despite the low air temperatures (even reaching –19°C, recorded 1.5 m above the ground), the survivorship was very high: all of the 18 queens used in the experiment survived, while the survival rate of workers was 61.9-100%, and for most colonies it exceeded 95%. The rate of survival in the nest sites aboveground and those experimentally buried in the soil was similar. Such a high survival rate in the nests situated at ground level could have resulted from the presence of snow cover during the strongest frost. The artificial nest sites used in the study provided safety for the ants; however, the real mortality during winter, e.g. connected also with predation or destruction of the nest sites, is a subject that needs further study.